2020
DOI: 10.1038/s41598-020-60452-1
|View full text |Cite
|
Sign up to set email alerts
|

A mouse model of pulmonary Mycobacteroides abscessus infection

Abstract: there is no preclinical mouse model to investigate pulmonary Mycobacteroides abscessus (formerly Mycobacterium abscessus) infection in an immunocompetent mouse strain, especially in the context of antibiotic testing and regimen development. We developed a mouse model of pulmonary M. abscessus infection using the aerosolized route of infection that leads to an increase in bacterial burden postimplantation and develops pathology as a result. in this mouse model, treatment with corticosteroid allows for initial p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 45 publications
2
49
0
Order By: Relevance
“…Foamy macrophages are a distinctive characteristic of granulomas associated with virulent mycobacteria; these cells have been observed in different inflammatory conditions, including infectious and noninfectious diseases, such as natural and experimental TB in particular [ 58 ]. The formation of foamy macrophages has been described in models of infection with M. abscessus both, in vitro [ 59 , 60 ], and in vivo [ 61 , 62 ]. It has been suggested that the induction of foamy macrophages results in an intracellular microenvironment that allows the persistence of mycobacteria, and that the fatty acids that accumulated in their cytoplasmic vacuoles represent a source of nutrients for the bacilli [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Foamy macrophages are a distinctive characteristic of granulomas associated with virulent mycobacteria; these cells have been observed in different inflammatory conditions, including infectious and noninfectious diseases, such as natural and experimental TB in particular [ 58 ]. The formation of foamy macrophages has been described in models of infection with M. abscessus both, in vitro [ 59 , 60 ], and in vivo [ 61 , 62 ]. It has been suggested that the induction of foamy macrophages results in an intracellular microenvironment that allows the persistence of mycobacteria, and that the fatty acids that accumulated in their cytoplasmic vacuoles represent a source of nutrients for the bacilli [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…GM-CSF -/, GKO or SCID mice) [11][12][13]. Moreover, corticosteroids were recently administered to immunocompetent mice to increase their susceptibility to the aereosolized pulmonary MA infection [25]. In our murine model, despite an initial protective high release of TNF-α and IFN-γ, granulomatous lung lesions (characterized by histiocytes, aggregates of foamy cells, neutrophils and lymphocytes) were present in the parenchyma around bronchi for about two months after MA infection, mimicking the damage observed in humans [23].…”
Section: Discussionmentioning
confidence: 99%
“…In TB drug and regimen development, mouse models have been pivotal for bridging the gap from in vitro to clinical studies (74). Ongoing efforts to develop and improve mouse models of M. abscessus lung infection have already shown promise (20, 21, 51, 75, 76), but nearly all are complicated by the lack of natural bacterial multiplication in the lungs. Thus, while this present series of in vitro studies indicates that a bedaquiline-rifabutin combination has promising activity against M. abscessus , further studies are needed to provide both the tools and the knowledge to translate the clinical relevance of these findings.…”
Section: Discussionmentioning
confidence: 99%